2017
DOI: 10.1177/0363546517713687
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Performance of a Novel, Anatomically Shaped, Total Meniscal Prosthesis Made of Polycarbonate Urethane: A 12-Month Evaluation in Goats

Abstract: This novel polycarbonate urethane implant may have the potential to become an alternative treatment for symptomatic patients with total meniscectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…It should be taken in to account that animal species differ not only in gross joint anatomy but also in details, such as chondrocyte density, cartilage thickness and metabolic differences, which will influence the outcome of the specific OA model 59,60 . Spontaneous OA has been reported for multiple large animal models and should be taken into account 54,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be taken in to account that animal species differ not only in gross joint anatomy but also in details, such as chondrocyte density, cartilage thickness and metabolic differences, which will influence the outcome of the specific OA model 59,60 . Spontaneous OA has been reported for multiple large animal models and should be taken into account 54,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-degradable synthetic solid polyurethane scaffolds were originally designed as total meniscus replacements, however a 2- year follow up study using dogs indicated that the polyurethane implant was not chondroprotective [82] , possibly due to the lack of scaffold degradation at 24 months [92] . Vrancken et al tested a synthetic solid, non-degradable, anatomically shaped polycarbonate urethane scaffold and compared it to the use of MAT in a biomechanical human cadaver model [93] and then a goat animal model [94] . Twelve-month follow-up after total meniscal replacement indicated that while the implant could not prevent the cartilage degeneration, the progression of damage was similar to MAT, in keeping with the results from the ex vivo human cadaver study.…”
Section: Biomaterials For Meniscus Tissue Engineeringmentioning
confidence: 99%
“…The application of a prosthetic meniscus device is yet another area of research in the field 101. Implants of this type, however, are highly difficult to design in view of the complicated biomechanical behaviour of the meniscus 13.…”
Section: Specific Populationmentioning
confidence: 99%